EDUCATION OF SEXUALLY TRANSMITTED DISEASES IN ADOLESCENTS AT SMKS KARYA RUTENG - Sriana Banul, Maria; Elsidianastika Trisnawati, Reineldis; Octaviani Laput, Dionesia; Sedista Manggul, Makrina; Angela Norce Halu, Silfia; Bening, Isabela (LPPM Univ. Ibn Khaldun Bogor, 2022)
The phenomenon of free sex has spread among teenagers, and has an impact on the increase in sexually transmitted diseases, so education on reproductive health, especially Sexually Transmitted Diseases (STD), should be informed to children, especially teenagers, both through formal and informal education. The activity was carried out at Vocational High School Karya Ruteng. The number of participants is 61 people. This activity aims to increase adolescents' knowledge at Vocational High School Karya Ruteng about Sexually Transmitted Diseases (STD) in the good, enough, and fewer categories. The method is to provide counseling, question and answer, and discussion with the participants. The level of adolescent knowledge at Vocational High School Karya Ruteng was assessed through the results of filling out questionnaires filled out by participants before and after the activity as well as the results of questions and answers at the end of the activities. The knowledge of participants after participating in this activity has increased. The increase in knowledge expecting to shape adolescent behavior to avoid free sex among adolescents so that unwanted pregnancies and increased transmission of sexually transmitted diseases do not occur.